STIGMATISATION: AN IMPEDIMENT TO COUNSELLING AND TESTING OF HUMAN IMMUNODEFICIENCY VIRUS (HIV) IN NIGERIA - Haruna, Abubakar Sadiq (Sokoto Educational Review, 2011)
Stigmatization is a pervasive problem that affects people, threatening individuals psychologically and physical well being. This paper presents stigmatization as an impediment to counselling and testing of Human Immunodeficiency Virus or Acquired Immune Deficiency Syndrome (HIV/AIDS). Theories of HIV discussed include the hunter's theory, the oral polio vaccine theory and the conspiracy theory. The main thrust of these theories is the assertion that HIV was transferred from chimpanzee to humans. Stigma can be caused by some factors as; insufficient knowledge of HIV/AIDS and fear of contagion. Several types and forms of HIV/AIDS stigma were equally discussed. For instance, a country’s laws regarding HIV/AIDS discriminate people living with it. Also discussed is the impact of stigma on the individual. For example, fear of prejudice, discrimination, discrediting and discounting impacts behaviour change, counselling and testing of HIV/AIDS. Recommendations offered suggests enacting of policies, use of improved skills and techniques as well as the initiation of programmes that would help in tackling the menace of HIV stigmatization in Nigeria.